2017
DOI: 10.4049/jimmunol.1601741
|View full text |Cite|
|
Sign up to set email alerts
|

Cutting Edge: Helminth Coinfection Blocks Effector Differentiation of CD8 T Cells through Alternate Host Th2- and IL-10–Mediated Responses

Abstract: Concurrent helminth infection potently inhibits T cell immunity; however, whether helminths prevent T cell priming or skew clonal recruitment and effector differentiation is not known. Using coinfection with two natural mouse pathogens, Heligsomosoides polygyrus and Toxoplasma gondii to investigate the negative impact of helminthes on the CD8 T cell response, we demonstrate helminth-induced suppression of IL-12-dependent differentiation of KLRG1+ effector CD8 T cells and IFNγ production. Nevertheless, reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…Indeed, helminth infections can down-modulate allergy or inflammatory bowel disease through various mechanisms 38 , but have also been involved in modulating the ability of the infected host to control virus infections. Several groups have shown using C57BL/6 mice that exposure to H. polygyrus or S. mansoni eggs enhanced reactivation from latency of MuHV-4 through changes in the IL-4/IFN-γ balance 10 and also that intestine dwelling helminths could alter effector CD8 + T cell responses against a subsequent viral 8 or protozoal infection 39 . Nevertheless, these studies did not investigate how helminths could affect bystander memory T cells such as the T VM compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, helminth infections can down-modulate allergy or inflammatory bowel disease through various mechanisms 38 , but have also been involved in modulating the ability of the infected host to control virus infections. Several groups have shown using C57BL/6 mice that exposure to H. polygyrus or S. mansoni eggs enhanced reactivation from latency of MuHV-4 through changes in the IL-4/IFN-γ balance 10 and also that intestine dwelling helminths could alter effector CD8 + T cell responses against a subsequent viral 8 or protozoal infection 39 . Nevertheless, these studies did not investigate how helminths could affect bystander memory T cells such as the T VM compartment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CD8 + T lymphocytes from patients with schistosomiasis presented a higher frequency of CTLA-4 than patients with leishmaniasis. In coinfections by the helminth Heligmosomoides polygyrus and the protozoan Toxoplasma gondii , the nematode-induced response sup-presses CD8 + T lymphocytes with decreased IFN-γ (Marple et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Co-infection with T. gondii in these mice was instead accompanied by a shift toward a non-protective helminth-specific Th1 response ( 44 ). Conversely, separate studies have shown that H. polygyrus co-infection can negatively impact upon CD8 + T cell differentiation and cytokine production in response to T. gondii infection ( 45 , 46 ). Conventional dendritic cells from the H. polygyrus co-infected mice also had reduced expression of IL-12 ( 46 ).…”
Section: Apicomplexan Parasitesmentioning
confidence: 99%